Análise de concordância entre os softwares Scpan e Radio Memory na identificação do período de crescimento puberal - Oliveira, Marília Michele Paixão de (2019)
Introduction: The identification of the pubertal growth period is used in dentistry, in the planning of cases to define the best time for the beginning of orthodontic treatment and in the area of endocrinology to evaluate the body development. With the development of applied technologies in the health area, methods are being developed to facilitate diagnosis and planning. In this context the software Scpan® was developed to identify the period of pubertal growth in which the patient is, through dental radiographs, which has been object of studies on its feasibility of use in clinical for the evaluation of pubertal growth. Objective: To analyze the agreement of the Scpan® software to identify the period of pubertal growth in panoramic radiographs in relation to the method of analysis by carpal radiography using Radiomemory® software. Methodology: This is a crosssectional study, inductive approach, descriptive-comparative procedure and direct documentation technique. The sample consisted of 100 pairs of panoramic radiographic images and carpales of the same individual, obtained from the digital archive of a Center of Radiology and Dental Documentation in the city of João Pessoa. The data used referred to the stages of pubertal growth by bone maturation in carpal radiographs using Radiomemory® software and second molar tooth mineralization using Scpan® software. Categorical categorical data were submitted to descriptive and inferential statistics using the Spearman correlation test and concordance analysis between Bland & Altman methods. Results: The sample distribution in the male sex was 49%, the mean age of the sample was 10.95 (± 2.07) years. The stages of pubertal growth were distributed in five categories; in the Scpan® software, stage 4 was the most frequent for teeth 17, 27, 37 and 47 with values of respectively 29%, 30%, 33% and 32%, respectively. In the Radio Memory® software method stage 2 expressed a frequency of 33%, followed by stages 3 and 4 with 19% and 18%, respectively; The variables related to the pubertal growth stage obtained by bone maturation and dental mineralization of the upper and lower second molars (17, 27, 37 and 47) present values for the Spearman correlation, respectively: r = 0.999568; 0.999556; 0.99943 and 0.999394. According to the Bland-Altman analysis The agreement found between the methods was high, with values for elements 17, 27, 37 and 47 respectively of 91%, 91%, 88% and 85% of the differences between the means were within the limits reliable. Conclusion: Good agreement between the values found for the evaluated methods was observed. In this way the Scpan® software can be considered as a viable tool to identify pubertal growth.